Exploring the effects of gastrointestinal digestion on phenolic profile and antioxidant activity: A new perspective on the biological potential of infusion of Eugenia pyriformis Cambess leaves - Dacoreggio M.V. (2024)
© 2024The influence of gastrointestinal digestion on phenolic compounds and antioxidant activity of E. pyriformis Cambess leaves infusion was investigated, along with assessing bioaccessibility and antidiabetic/antihypertensive effects via enzyme inhibition. The study aimed to understand how digestion affects the bioactive compounds and health benefits of uvaia leaf infusion. A total of 26 phenolic compounds, including phenolic acids, flavonoids, and phenols, were identified in both undigested and digested samples across oral, gastric, and intestinal phases. Variations in phenolic compound profiles and concentrations were observed during in vitro gastrointestinal digestion. Despite a reduction in antioxidant potential post-digestion, the infusion retained high antioxidant capacity, primarily attributed to phenolic acids like 2.5-DHBA, ferulic acid, and p-coumaric acid. The infusion exhibited significant inhibition percentages for antidiabetic (14–21 %) and antihypertensive (11 %) activities. These findings underscore the potential of uvaia leaf infusion as a rich source of antioxidant phenolics with promising phytotherapeutic applications for diabetes mellitus and hypertension. The study highlights the importance of considering gastrointestinal digestion in assessing the bioavailability and health effects of plant-derived bioactive compounds, emphasizing their potential as functional foods or supplements for managing chronic diseases.